2010
DOI: 10.1038/cddis.2010.24
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase Cθ is required for cardiomyocyte survival and cardiac remodeling

Abstract: Protein kinase Cs (PKCs) constitute a family of serine/threonine kinases, which has distinguished and specific roles in regulating cardiac responses, including those associated with heart failure. We found that the PKCθ isoform is expressed at considerable levels in the cardiac muscle in mouse, and that it is rapidly activated after pressure overload. To investigate the role of PKCθ in cardiac remodeling, we used PKCθ−/− mice. In vivo analyses of PKCθ−/− hearts showed that the lack of PKCθ expression leads to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…Knockout mice for PKCθ develop dilated cardiomyopathy accompanied by reduced fractional shortening, increased fibrosis, and enhanced levels of cardiomyopathy markers such as ANF, as well as activation of p38 and JNK pathways [71]. In contrast to the dramatic phenotype of PKCθ knockouts, genetic ablation of PKCδ and/or PKCε did not result in a profound postnatal cardiac baseline phenotype [72][73][74][75].…”
Section: Novel Pkcsmentioning
confidence: 94%
“…Knockout mice for PKCθ develop dilated cardiomyopathy accompanied by reduced fractional shortening, increased fibrosis, and enhanced levels of cardiomyopathy markers such as ANF, as well as activation of p38 and JNK pathways [71]. In contrast to the dramatic phenotype of PKCθ knockouts, genetic ablation of PKCδ and/or PKCε did not result in a profound postnatal cardiac baseline phenotype [72][73][74][75].…”
Section: Novel Pkcsmentioning
confidence: 94%
“…PKC ε may also inhibit apoptosis by phosphorylating Connexin-43 at Ser262 and inhibit interaction between Connexin-43 and Kir6.1, a pore-forming subunit of ATP-sensitive potassium channels [207]. Another PKC isoform, PKC θ , has been shown to be protective based on the observation that global deletion of PKC θ led to p38/JNK activation and ventricular dilation after pressure overload, and PKC θ −/− cardiomyocytes were more susceptible to apoptosis upon stimulation with PE and hypoxia [208]. Treatment with PKC inhibitor chelerythrine or BIM-1 abolished fibroblast growth factor-2 (FGF-2) mediated protection against DOX-induced apoptosis, suggesting that PKC activation is an important prosurvival mechanism downstream of FGF-2 [209].…”
Section: Pkcmentioning
confidence: 99%
“…In skeletal muscle, we and others showed that PKCθ is mostly involved in mediating signaling pathways regulating fetal and early post-natal growth and maturation ( Madaro et al, 2011 , Madaro et al, 2013 , Marrocco et al, 2014 , Messina et al, 2010 , Zappelli et al, 1996 ). Employing PKCθ −/− mice, we also showed that PKCθ maintains the correct structure and function of the heart by preventing cardiomyocyte cell death in response to work demand and to neuro-hormonal signals, to which heart cells are continuously exposed ( Paoletti et al, 2010 ).…”
Section: Introductionmentioning
confidence: 96%